Emerging Cases of Hepatitis C Virus and Human Immunodeficiency Virus Co-infection Among Narcotics Abusers in Pondok Indah Hospital, Jakarta - Chaidir Aulia (The Indonesian Society for Digestive Endoscopy, 2005)
Background: Narcotics and psychoactive substances abuse, particularly by intravenous route, currently is a major health problem affecting young Indonesian people. Consequently, there is an increasing incidence of blood-borne viral diseases, including hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infections. This study was aimed to investigate the prevalence of HCV and HIV co-infection among narcotics abusers in Pondok Indah Hospital, Jakarta. Method: This was a cross-sectional study in Pondok Indah Hospital, Jakarta using patients’ medical records. Data from patients with the diagnosis of mental and behavioral disorders due to various psychoactive substances and HIV-related diseases were retrieved to obtain demographic characteristics, history of drug abuse and serological testing. Patients were excluded if there were another organic mental disorders found or a history of blood transfusion prior to infection. Results: There were 157 cases of drug abuse collected between January 2000 and May 2005, 85.4% were men and their median age was 24 years old. The peak age group was 21-25 years old. Injection drug users (IDUs) were found in 72% of cases. Anti-HCV total antibody was found in 45.2% cases, including 2 non-IDUs, while anti-HIV antibody and combined anti-HCV/anti HIV antibodies were found in 13.4% and 7.6% cases, respectively. Anti-HCV positive patient are significantly younger than anti- HCV negative patients (27.9 + 8.2 vs. 23.7 + 4.4 years, p 0.001), while the duration of use was not significantly correlated with HCV infection. Neither age nor duration of use was statistically significant with the presence of anti-HIV antibody. However, there is a significant correlation between the duration of drug abuse with HCV and HIV co-infection (6.0 + 3.0 vs. 4.1 + 2.8 years, p = 0.027). Conclusion: The prevalence of HCV and HIV co-infection among narcotics abusers in Pondok Indah Hospital was 7.6%. The emerging cases of hepatitis C and HIV infections during the last several years was significantly related to the increasing numbers of narcotics abusers. Keywords: hepatitis C virus, human immunodeficiency virus, co-infection, injection drug users